Implementasi Manajemen Risiko Berdasarkan ISO 31000:2009 pada Program Perawatan Mesin di Area Workshop PT. X - Sari Delima Fitri; Dina Lusiana Setyowati; Krispinus Duma (Faletehan Health Journal, 2019)
Machine maintenance programs in workshop area are high risk working units in terms of work accidents. This research purpose was to explore implementation of risk management based on ISO 31000:2009 of machine maintenance program in workshop area. This research was a qualitative research according to ISO 31000:2009. The informants in this research were head workshop as main informant, maintenance department head as key informant and worker in workshop as supporting informant. The engine maintenance program in the workshop area consists of 3 work stages namely fabrication, assembly and service (finishing). The results showed that from hazard identification results found physical hazard, chemical hazard, biological hazard, ergonomic hazard and psychological hazard. Risk analysis results were not found to be hazards with extreme risk, 3 dangers on the level of high risk, 13 dangers in the level of moderate risk hazards and 11 dangers in the level of low risk. Forms of risk treatment is in the initial treatment using risk mitigation methods for each of the risks faced, then the next treatment includes risk transfer, avoiding risk and accepting risks. Based on the result of a defined risk treatment, the recommendation or treatment of possible risks is an effective control measure and appropriate treatment in dealing with various possible risks.